Из Сибири - Чехов Антон Павлович (1978)
Экземпляры: Селтинская районная библиотека (аб) (20221003) / Инвентарный номер: 3602 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Ч-56 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1